2021
DOI: 10.3390/tropicalmed6040177
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Cases in a Tertiary Hospital in Kuala Lumpur, Malaysia: A 16-Year (2005–2020) Retrospective Review

Abstract: While there has been a tremendous decline in malaria disease burden in the remote parts of Malaysia, little is known about malaria incidence in its urban localities. This study aimed to analyze trends of malaria cases in urban Kuala Lumpur, Malaysia. All suspected cases presented to a university hospital in Kuala Lumpur from January 2005 to December 2020 were examined by microscopy. Infection status was analyzed using descriptive statistics and curve estimation analysis. Of 3105 blood films examined, 92 (3%) w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The decline is attributed to enhanced coverage of indoor residual spraying (IRS) and better passive case detection and management practices ( WHO, 2015 ). Subsequently, the program was strengthened, and malaria has been on the national list of notifiable diseases since 1988 ( Dian et al., 2021 ). Despite having zero indigenous human malaria cases in Malaysia since 2018 ( WHO, 2020 ; Dian et al., 2022b ), malaria is still one of the public health problems.…”
Section: Discussionmentioning
confidence: 99%
“…The decline is attributed to enhanced coverage of indoor residual spraying (IRS) and better passive case detection and management practices ( WHO, 2015 ). Subsequently, the program was strengthened, and malaria has been on the national list of notifiable diseases since 1988 ( Dian et al., 2021 ). Despite having zero indigenous human malaria cases in Malaysia since 2018 ( WHO, 2020 ; Dian et al., 2022b ), malaria is still one of the public health problems.…”
Section: Discussionmentioning
confidence: 99%
“…Concisely, Sarawak maintained a high number of imported cases (greater than 160 cases annually) from 2013 to 2017. Previous surveillance-based studies in Peninsular Malaysia suggested that imported malaria cases are mainly attributable foreign migrant workers [18][19][20]. To date, the demographic profile of imported malaria patients in Malaysia, especially in Sarawak, has not been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the decline, approximately 627,000 malaria deaths were still recorded worldwide in 2020, with children under five and service disruptions during the COVID-19 pandemic accounting for 77% and 68% of all malaria deaths, respectively [2]. Malaria is still considered a public health problem in Malaysia and has been on the list of the national notifiable diseases since 1988 [3]. Since the early nineteenth century, it has been recognized as a serious disease in Peninsular Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the significant decrease in human malaria, the emergence of simian malaria is a major public health problem in the less developed areas of Malaysia. In particular, it is a problem among the hard-to-reach indigenous populations (i.e., Orang Asli) in Peninsular Malaysia and the remote interior communities in Malaysian Borneo [3,5,7,8]. In 2019, Malaysia recorded 3222 zoonotic malaria with six fatalities [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation